Assessment of awareness, attitude, knowledge and application towards dental ergonomics and musculoskeletal disorder among dental students and professionals in Ahmedabad - Solanki, Harsh; Sodani, Vasudha; Sarvaiya, Bhumi; Chauhan, Keyur; Shah, Reetu (International Journal Of Community Medicine And Public Health, 2024)
Background: Dental ergonomics, the science of optimizing the workplace for dental professionals, is essential for preventing musculoskeletal disorders (MSDs) and ensuring the long-term health of dental practitioners. Methods: A cross-sectional survey aimed to assess the awareness and attitude of dental students and professionals towards dental ergonomics, with the collected data subsequently subjected to rigorous statistical analysis. Results: A 51% of dental students and 78% of dental professionals were aware about dental ergonomics. Only 12% of the dental students have attended a course regarding dental ergonomics, 73% of the dental professionals among study population have experienced musculoskeletal pain due to dental practice. Conclusions: The survey revealed that dental students exhibited lower awareness of dental ergonomics compared to dental professionals, with a notable discrepancy in the implementation of ergonomic principles. Additionally, a significant prevalence of pain related to MSDs was observed among the dental professionals surveyed.